Structural shift in global natural gas markets: Demand boom in Asia, supply shock in the US - Franziska Holz; Philipp M. Richter; Christian von Hirschhausen (DIW Economic Bulletin, 2013)
The significance of natural gas is on the rise due to the restructuring and decarbonization of energy systems worldwide. Natural gas is widely available and flexible as it can be used in electricity generation, manufacturing, transport, and private households. Compared to other fossil fuels, natural gas produces relatively low carbon dioxide emissions during combustion. For this reason, the natural gas sector also has an important supportive role to play when it comes to the European energy transition towards renewable energies. Against this backdrop, DIW Berlin has examined the potential of the global natural gas market and carried out model-based analyses of possible scenarios for meeting different climate change targets. The structural shift in the international natural gas market that has been observed for some years now is also set to continue in the medium and long term. While the Arab states of the Persian Gulf, particularly Qatar, will remain swing suppliers due to their geographical location, Russia's significance in supplying Europe will decline in the future. New techniques such as fracking enable the exploitation of unconventional natural gas resources, which could potentially see the US become a strong natural gas exporter and also give other regions around the world the opportunity to extract their own natural gas. However, in Europe, the potential for additional production of domestic resources by extracting shale gas through fracking is rather limited for technical reasons and due to a lack of political support in the context of an adequate international natural gas supply. Asian demand for natural gas is expected to strongly rise as a result of the ever-increasing appetite for energy generated by economic growth. This demand region will absorb the major share of future natural gas trade. In Europe, the situation could develop along a number of different trajectories, depending on whether natural gas is used as a bridge fuel in the transition toward an energy system based on renewable energies or as a complement to fluctuating renewable power generation in the long term.
Keywords: Q31; Q47; Q54; 330; natural gas; resources; reserves; trade; Asia; Europe